Mechanism of carbon deposition within char derived from oil palm empty fruit bunch - Rozhan, Alya Naili; Hairin, Assayidatul Laila Nor; Mohd. Salleh, Hamzah; Purwanto, Hadi (American Institute of Physics Inc., 2019)
This paper describes the reaction mechanism to deposit pyrolytic carbon within porous body of char derived from oil palm empty fruit bunch (EFB) via an integrated pyrolysis-tar decomposition process, which employs chemical vapor infiltration method. This process was developed to produce a value-added EFB-derived char and to make EFB able to be utilized as a supplementary solid biofuel. The product, namely carbon-deposited char, was characterized in comparison with metallurgical coke breeze used in iron-steel industry.